ILMU-ILMU USHULUDIN MENJAWAB PROBLEMATIKA UMAT ISLAM DEWASA INI - Ibrahim, Farid Wajdi (UIN Ar-Raniry, 2014)
Abstract: The interpretation of ushuluddin is how the humanÃ‚Â relationship with God and man to man to avoidinequality, the human beings should be able to put himself as aservant of God ('abd) are always subjecting themselve stoper form the ritualworship. However, as a zon human politicon the human being should also capable in understanding social phenomena that occurinthe community, andprovide the solutions to the problems that occurin the community in the real life, as well ashow to create the social conditions to be prosperous society that is blessed by the Almighty.